Dampak Kecerdasan Buatan dalam Pembelajaran Matematika dan IPA: Pengembangan Kurikulum yang Responsip terhadap Era Digital - Nurmaliati; Rendi Hadian A. Tamagola; Al Ikhlas; Efriana Jon; Novy Trisnani; Ira Wulan Sari (Academy of Education Journal, 2026)
The rapid development of Artificial Intelligence (AI) has significantly influenced various sectors, including education, particularly in Mathematics and Science learning. The integration of AI into instructional processes presents both opportunities and challenges, especially regarding curriculum readiness in responding to the demands of the digital era. The main problem addressed in this study is how AI impacts the learning of Mathematics and Science and how a responsive curriculum can be developed to accommodate these technological advancements. This study aims to analyze the role of AI in enhancing the effectiveness of Mathematics and Science learning, identify emerging competencies required by students, and formulate principles for curriculum development that align with AI integration. The research employs a systematic literature review method by examining scholarly articles, research reports, and educational policy documents relevant to AI and curriculum development. The results indicate that AI contributes positively to personalized learning, improved understanding of abstract concepts, enhanced problem-solving skills, and increased digital literacy among students. Furthermore, AI encourages a shift in the teacher’s role from information transmitter to learning facilitator and mentor. However, effective implementation requires curriculum adjustments that emphasize critical thinking, digital ethics, and human–technology collaboration. In conclusion, developing a curriculum that is responsive to the digital era necessitates the pedagogical, sustainable, and ethical integration of artificial intelligence, with a strong focus on fostering 21st-century competencies.